The effect of match fatigue in elite badminton players using plantar pressure measurements and the implications to injury mechanisms - Valldecabres, R.; Richards, J.; Benito, A.-M. (Sports Biomechanics, 2022)
The purpose of this study was to investigate the differences in plantar pressure under the lead and trail foot between two lunge tasks to the net in the dominant (LD) and non-dominant (LND) directions, and to explore how fatigue affects the plantar pressure patterns whilst performing movements before and after a competitive match. Peak and mean pressure were measured with the Biofoot-IBV in-shoe system from five repetitions of each task, with sensors positioned under the calcaneus, midfoot and phalanges on the lead and trail foot. Data were collected pre and immediately post-playing an official first national league competition match. The study was conducted with a sample of thirteen first league badminton players. A 2 × 2 repeated ANOVA found significant differences between the two tasks and between pre- and post-match (fatigued state). Players also had different foot pressure distributions for the LD and LND tasks, which indicated a difference in loading strategy. In a fatigued state, the plantar pressure shifted to the medial aspect of the midfoot in the trail limb, indicating a reduction in control and a higher injury risk during non-dominant lunge tasks.